Using the consolidated framework for implementation research to evaluate a model of community-engaged research in advance care planning - Erika VanDyke; William Calo; Benjamin Levi; Amy Tucci; Lauren Jodi Van Scoy (PLoS ONE, 2026)
Background Advance care planning (ACP) is the process of discussing one’s goals and wishes for end-of-life care with loved ones or clinicians and then completing an advance directive (AD). Our Community-Based Delivery Model (CBDM) has demonstrated success in engaging these communities, yet the implementation mechanisms behind its effectiveness remain unclear. This study utilized the Consolidated Framework for Implementation Research (CFIR) to evaluate the CBDM in the context of the Project Talk Trial (PTT), a national randomized controlled trial of ACP interventions. Methods This study employed a two-pronged approach. First, CFIR was used to systematically map the CBDM, defining domains and constructs relevant to the intervention’s implementation in diverse community contexts. Second, semi-structured interviews with 24 community hosts who facilitated PTT events provided qualitative insights into the “inner setting,” “outer setting,” and “implementation process” domains. Deductive coding and thematic analysis were used to identify key implementation strategies and challenges. Results The CFIR mapping revealed three critical features driving the CBDM’s success: the transfer of resources between outer and inner settings, the central role of community hosts in bridging these domains, and the flexibility to adapt to local contexts. Semi-structured interviews identified five themes, including hosts’ use of relational connections, teaming and engaging strategies, and culturally tailored approaches, which facilitated implementation. Notably, rural hosts exceeded recruitment goals, challenging the notion that rural populations are “hard to reach”. Conclusions This approach provides actionable insights for improving ACP efforts in communities settings. The integration of CFIR mapping and empirical data highlights the CBDM’s potential as a scalable model for implementing community-engaged health interventions.